HIV self-testing knowledge, attitudes, and practices among Asian-born gay, bisexual, and other men who have sex with men in Australia: a qualitative study - Zhang, Ying; Chow, Eric P. F.; Sudarto, Budiadi; Wang, David; Stoove, Mark; Medland, Nicholas; O'Donnell, Darryl; Keen, Phillip; Ong, Jason J.; Phillips, Tiffany R. (Frontiers in Public Health, 2024)
Background: Achieving virtual elimination of HIV transmission in Australia requires a combination of high treatment rates and high testing coverage among individuals at risk of acquiring HIV. HIV self-testing (HIVST) is an additional testing approach for key populations. Objective: We aimed to examine the knowledge, attitudes, and practices of HIVST among Asian-born gay, bisexual and other men who have sex with men (GBMSM). Methods: This qualitative study used semi-structured interviews of overseas-born GBMSM of Asian background in Australia. Participants were recruited from personal networks, social media platforms, snowballing, and the Melbourne Sexual Health Centre. Twenty-five participants were purposively sampled with a range of ages and previous levels of experience with HIVST. Interview transcripts were imported into Nvivo 12 for data management. Results: The age of the participants ranged from 19 to 44 years, with a median of 30 years. Most were unaware of HIVST before the interview, and only a few had ever used one. All had limited sexual health knowledge (i.e. HIV testing, PrEP) before they arrived in Australia. Upon learning about HIVST during the interview, many expressed willingness to use HIVST, but in limited circumstances, such as travelling overseas, interim testing while taking on-demand PrEP, and point-of-sex testing. Almost all were open to distributing HIVST to their casual partners or friends, especially those they knew who engaged in high-risk sexual practice (i.e., condomless anal sex) and were not engaged in sexual healthcare. About half still preferred conventional serology testing because of regular HIV testing as part of PrEP prescription and the need for testing for other sexually transmitted infections. Conclusion: HIVST may be an acceptable additional testing approach for HIV testing among Asian-born GBMSM. Peer education and secondary distribution may help raise HIVST awareness and use.